2005
DOI: 10.1097/00008877-200509000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1 receptor dependent effects of the NMDA antagonist phencyclidine in the social withdrawal model of schizophrenia

Abstract: Clinical and laboratory findings suggest that cannabinoid signalling is implicated in schizophrenia. However, the interaction remains poorly understood, as data are often contradictory. Here we investigated wild-type (WT) and cannabinoid CB1 receptor-knockout (CB1-KO) mice in the phencyclidine-induced social withdrawal model of schizophrenia. N-methyl-D-aspartate (NMDA) antagonists (including phencyclidine) induce psychotic symptoms in humans, and are used to model schizophrenia in a variety of experimental co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 58 publications
3
17
0
1
Order By: Relevance
“…Furthermore, mutations in CNR1 (a gene encoding CB1R) have been associated with a susceptibility to schizophrenia in human genetic studies (Leroy et al, 2001;Ujike et al, 2002). Studies of mutant mice with the CNR1 gene deletion revealed that the schizophrenia-like behavioral responses to an NMDAR inhibitor depended on a functional CB1R (Haller et al, 2005). Thus, our data indicating an abnormality in the eCB system in a schizophrenia model are consistent with the initial findings in humans and rodents.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, mutations in CNR1 (a gene encoding CB1R) have been associated with a susceptibility to schizophrenia in human genetic studies (Leroy et al, 2001;Ujike et al, 2002). Studies of mutant mice with the CNR1 gene deletion revealed that the schizophrenia-like behavioral responses to an NMDAR inhibitor depended on a functional CB1R (Haller et al, 2005). Thus, our data indicating an abnormality in the eCB system in a schizophrenia model are consistent with the initial findings in humans and rodents.…”
Section: Discussionsupporting
confidence: 88%
“…Generally, CB 1 receptor agonists reduce the hyperlocomotion induced by amphetamine, quinpirole and cocaine (Gorriti et al, 1999 ;Marcellino et al, 2008 ;Moreira and Guimarães, 2005 ;Przegaliń ski et al, 2005), although not always by acting via CB 1 receptors ; CB 1 antagonists can reduce, increase or not affect the hyperlocomotion induced by different dopaminergic agents (Corbillé et al, 2007 ;Ferrer et al, 2007 ;Madsen et al, 2006 ;Masserano et al, 1999 ;Poncelet et al, 1999). Moreover, CB 1 gene deletion reduces the hyperlocomotion induced by both dopaminergic agents and phencyclidine (PCP) (Corbillé et al, 2007 ;Haller et al, 2005). Regarding sensory motor information gating processes, generally CB 1 receptor agonists disrupt pre-pulse inhibition (PPI) (Bortolato et al, 2005 ;Hajó s et al, 2008 ;Martin et al, 2003 ;Schneider and Koch, 2005), whereas cannabidiol and the CB 1 receptor antagonist, SR141716A, reverse MK801-or PCP-induced PPI deficit (Ballmaier et al, 2007 ;Long et al, 2006 ; but see also Martin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Acute phencyclidine (PCP) administration is a well-accepted preclinical model reproducing some aspects of schizophrenia, since it induces locomotor activation, stereotyped behaviors, and reduced social interactions in wild-type animals. Interestingly, PCP-induced behavioral alterations were different in CB1 ko mice (Haller et al 2005), since reduced locomotion, greater enhancement in ataxia, and stereotypies as well as no alterations in social behavior were observed. As social disruption and stereotypy are believed to model, respectively, negative and positive symptoms of schizophrenia, it can be hypothesized that the CB1r may contribute differently to these two types of symptoms, possibly inhibiting positive but facilitating negative ones.…”
Section: Schizophreniamentioning
confidence: 93%
“…However, the chronic administration of AM251, a CB1 receptor antagonist, also counteracted the increase in aggressive behaviors observed in rats reared in isolation (Zamberletti et al 2010). Accordingly, genetic deletion of the CB1 receptor prevented PCP-induced social deficits in mice (Haller et al 2005). So far only a few studies have examined the effect of a pharmacological modulation of the ECS on cognitive deficits in animal models of schizophrenia.…”
Section: Pharmacological Modulation Of the Ecs As A New Opportunity Fmentioning
confidence: 99%